Reducing Liquidation Delays through Documentation and Communication in a Construction Company in the Philippines - Cornel, Jessa Mae L; Briones , Jesus P; Baldovino , Flormando P; Manalo, Lalaine V (Research Synergy Foundation, 2025)
Efficient documentation and communication are crucial for minimizing liquidation delays in the construction industry. This descriptive-quantitative study explored the documentation practices and communication strategies on liquidation delays within a Philippine construction company. Using a researcher-structured questionnaire, data were collected from 30 administrative professionals across departments where activities are directly related to the liquidation process of the company. The data were analyzed using frequency, percentage, standard deviation, weighted mean, and ANOVA. The findings revealed that the company's systems, relative to their documentation and communication approaches, are generally effective, though there are still some challenges that sometimes occur to cause delays in liquidation, such as incomplete documentation, poor communication, and delayed approvals, which contribute to inefficiencies. Moreover, the study found that there were significant differences in the perceptions of employees on liquidation delays across departments, and in the communication strategies across work bases. On the other hand, it was verified that demographic factors such as age and length of service do not influence the employees’ perceptions of the liquidation process in terms of documentation practices, liquidation delays, and communication strategies of the construction company. In reference to the findings of the study, strategies for optimizing liquidation processes through documentation and communication were proposed. Overall, this study provides valuable insights for construction firms looking to optimize their operations, enhance documentation practices, and improve interdepartmental coordination. By implementing recommendations from this study, similar companies can better manage liquidation processes, reduce delays, and ensure timely project execution in the Philippine construction sector.